Characterisation and structural transformation of yttria dispersed austenitic steel through VHP. Issue 13 (2nd September 2021) - Arun Prasad, M.; Pavithra, E.; Dharmalingam, G.; Siva Prakasham, D.
Abstract : Two different alloys were developed from the mixtures of pre-alloyed powders consisting of ferroalloys to get the required composition of austenitic stainless steel via the powder metallurgy technique along with the presence and absence of Y2 O3 . The subsequent mechanical alloyed powders were subject to vacuum hot pressing at 1200°C. The samples were subject to microstructural characterisation post-vacuum hot pressing process. With the addition of yttria, the structure of the grains was fine for the mechanical alloyed vacuum hot pressed samples. The TEM analysis revealed the presence of heterogeneous distribution of yttria particles along the grain boundaries. With the addition of yttria within the metal matrix, the hot pressed density was increased marginally.